TEACHER’S PROBING QUESTIONS IN THE EFL CLASSROOM AT A HIGH SCHOOL (RETAIN, 2020)
This study meant to try to find the teacher’s probing questions in EFL classroom language. In specific, this research intends 1. To elucidate the teacher's probing questions for clarification. 2. To elucidate the teacher's probing questions about different viewpoints. 3. To elucidate the teacher's probing questions to probe pupils' assumptions. 4. To elucidate the teacher's probing questions to probe pupils’ reason. 5. To elucidate the teacher's probing questions to probe evidence. 6. To elucidate the teacher’s probing questions to probe implications and purposes. This study uses qualitative descriptive. The English teacher of a high school was the subject of this study. The data obtained by observing the subject. The technique utilized in this study is by carrying out unstructured observation. The outcomes of this study demonstrated that the teacher employed all of those six probing questions. The teacher applied numerous probing techniques, those are basic probe, explanatory probe, focused probe, silent probe, drawing out, giving ideas, and mirroring, but some of them did not work for students. Probing questions most often used in this case was probing questions for clarification. The probing technique which typically applied by the teacher was an explanatory probe. Keywords: Classroom language, Questions, Probing questions.